Emblematic Elegance: A Journey through the Types of Formal Events - Abdulazizov Dovudbek, Mahamadiyeva Muhlisa (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Embark on a captivating expedition through the sphere of formal events, unraveling the distinctive nature and inspiration behind various gatherings that resonate with elegance, prestige, and cultural significance. This article delves into the multifaceted realm of formal events, encompassing galas, ceremonies, banquets, and receptions, each bearing unique hallmarks of grandeur, tradition, and commemoration.